PROBLEMS OF SYSTEMIC LUPUS ERYTHEMATOSUS DIAGNOSTICS - Talash, V.V. (World of Medicine and Biology, 2025)
Systemic lupus erythematosus is a chronic systemic connective tissue disease of unknown etiology, which is often accompanied by multiorgan involvement with the development of complications. Given the heterogeneity of the clinical picture, the high probability of developing serological abnormalities, establishing the diagnosis is a multidisciplinary problem. The low rates of morbidity and prevalence of this disease in Ukraine, compared to the global rates, indicate insufficient and untimely detection of systemic lupus erythematosus in patients. The purpose of the study was to analyze information on the features of systemic lupus erythematosus diagnosis, diagnostic criteria to develop further prospects for developing an algorithm for its diagnosis. On the basis of literary data, the article presents modern concepts of etiology and pathogenesis, clinical manifestations of systemic lupus erythematosus, highlights the main difficulties in diagnosis. The article presents a brief analysis of systemic lupus erythematosus study history, an overview of modern possibilities of its laboratory diagnosis, and clinical criteria for establishing a diagnosis, which will allow doctors to establish a timely diagnosis and prescribe adequate therapy, thereby improving the detection rates of systemic lupus erythematosus and increasing the quality and life expectancy of patients.
Keywords: systemic lupus erythematosus; juvenile systemic lupus erythematosus; lupus nephritis; antinuclear antibodies; antibodies to double-stranded DNA; nephrobiopsy